1999
DOI: 10.1177/000456329903600506
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin and Immunoglobulins are More Useful Markers of Disease Progression in HIV than Neopterin and Adenosine Deaminase

Abstract: Reference change values of six biochemical quantities (beta 2-microglobulin, neopterin, adenosine deaminase and immunoglobulins IgA, IgG and IgM) have been established in asymptomatic human immunodeficiency virus (HIV)-infected patients following the method described by Harris and Yasaka in 1983. Patients included in the evaluation were classified as A1, A2 or A3 according to the classification of the Centers for Disease Control (CDC) (January 1993). All patients were followed-up quarterly, with a minimum of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, an increase in B2M is not speci¢c to a fall in GFR since it is elevated in viral infections, including HIV, re£ecting lymphocyte turnover. 7 Furthermore, it has been shown that serum B2M re£ects changes in lymphocyte activation in post-transplant patients. 8 Even though this test is available in our laboratory it has been ruled out for the detection of a reduction in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in B2M is not speci¢c to a fall in GFR since it is elevated in viral infections, including HIV, re£ecting lymphocyte turnover. 7 Furthermore, it has been shown that serum B2M re£ects changes in lymphocyte activation in post-transplant patients. 8 Even though this test is available in our laboratory it has been ruled out for the detection of a reduction in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study compared β 2 microglobulin, immunoglobulin A, G, and M, adenosine deaminase, and neopterin levels above normal range as predictors of clinical or immunological deterioration in 256 patients with HIV infection. Changes in β 2 microglobulin levels showed the greatest sensitivity to detect worsening (43%) with neopterin slightly less sensitive (41.9%) followed by immunoglobulin levels (26.8–35.2%) and adenosine deaminase levels with 21.8% having the lowest sensitivity [ 28 ].…”
Section: Neopterin Release In Viral Infectionsmentioning
confidence: 99%
“…The constitutively expressed subunit is a sensitive but nonspecific parameter of inflammation and infection (Fuchs et al, 1991). β-2 M concentrations in OMT have shown good correlation with serum levels (Nishanian et al, 1998) and may show greater sensitivity than neopterin in detecting clinical or immunological deterioration (Martinez-Bru et al, 1999).…”
Section: Question 3: Can Salivary Molecules Be Useful As Markers For mentioning
confidence: 99%